Circular RNA SESN2 aggravates gestational trophoblast cell damage induced by high glucose by binding to IGF2BP2. Issue 2 (9th January 2023) - Huang, Xin; Guo, Linlin
Abstract: Gestational diabetes mellitus (GDM) is a common disease in pregnant women that threatens maternal and fetal health. Circular RNAs (circRNAs) have been considered potential diagnostic markers for GDM and affect trophoblast cell phenotypes. This study aimed to explore the effect of circSESN2 on high glucose (HG)‐treated trophoblast cells. Peripheral blood and placental tissues were taken from patients with GDM, in which circSESN2 and IGF2BP2 levels were detected by quantitative reverse transcription polymerase chain reaction and/or western blot. HTR‐8/SVneo cells were treated with 25 mM glucose and transduced with circSESN2 or IGF2BP2 knockdown vectors. HTR‐8/SVneo cell viability was evaluated by MTT assay, cell migration by scratch test, and cell invasion by transwell assay, IL‐1β, IL‐6, TNF‐α, malondialdehyde, and superoxide dismutase levels by ELISA or kits, and reactive oxygen species levels by DCFH‐DA probes. The binding between circSESN2 and IGF2BP2 was verified by RNA pulldown and RIP assays. CircSESN2 and IGF2BP2 were overexpressed in GDM patients. Suppressing circSESN2 or IGF2BP2 increased HTR‐8/SVneo cell invasion and migration, decreased cell apoptosis, and reduced pro‐inflammatory cytokine release and oxidative stress injury. CircSESN2 bound IGF2BP2 and IGF2BP2 overexpression accelerated HG‐induced HTR‐8/SVneo cell damage despite circSESN2 knockdown. Collectively, circSESN2 exacerbated HG‐induced trophoblast cell damage by binding IGF2BP2 and upregulating its protein expression.